PERANCANGAN APLIKASI SISTEM PENCATATAN AKUNTANSI PADA PT. LAGENDA AGRO BATAM MENGGUNAKAN CODEIGNITER - Heru Wijayanto Ariandono; Ricky Andi Kurniawan (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
PT Lagenda Agro Batam or often referred to as Lagenda Park is a business that trades guava honey. PT Lagenda Agro Batam was founded in Lagenda Malaka in 2018 by Mrs. Siu Lang. However, the recording system at PT Lagenda Agro Batam still uses a simple accounting recording system, namely manual recording of all sales, purchases, and inventory stock transactions. So that the recording of transactions carried out has not been neatly arranged and can cause recording and calculation errors it can cause material losses. This study aims to provide the right solution to the problems faced by PT. Legenda Agro Batam in recording sales, purchases, and inventory transactions. The method used in this research is the Agile method, while the data collection technique uses observation and interviews. This accounting record system is developed using Codeigniter and uses XAMPP as a localhost webserver. The existence of a website-based accounting recording system is the best solution to facilitate the recording of accounting and financial reports at PT. Lagenda Agro Batam.